Positivism and Its Implications for Legal Science and Law Enforcement - Rilya, Muhammad Avin Athalla; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
This study aims to critically analyze the concept of positivism—both as a paradigm in the philosophy of science and as a school of thought in legal theory (legal positivism)—and examine its profound implications for the development of science (particularly the social sciences) and law enforcement practices. Positivism, which emphasizes empirical data, observation, verification, and a clear separation between fact (is) and value (ought), has shaped modern scientific methodology. However, when applied to law, legal positivism (as advocated by Austin and Kelsen) limits legal validity to formal procedures and competent authorities, ignoring moral considerations or substantial justice. Using normative-empirical research methods and a comprehensive literature review, it is found that the dominance of positivism in science fosters methodological objectivity, but in law enforcement, it can produce procedural legitimacy that is vulnerable to justice criticism. The main implication is the emergence of tension between the legal certainty promised by positivism and the pressing demands of substantive justice.